2022
DOI: 10.3390/antiox11050879
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of N-Acetylcysteine on Lipopolysaccharide-Induced Respiratory Inflammation and Oxidative Stress

Abstract: As the leading cause of bovine respiratory disease (BRD), bacterial pneumonia can result in tremendous losses in the herd farming industry worldwide. N-acetylcysteine (NAC), an acetylated precursor of the amino acid L-cysteine, has been reported to have anti-inflammatory and antioxidant properties. To explore the protective effect and underlying mechanisms of NAC in ALI, we investigated its role in lipopolysaccharide (LPS)-induced bovine embryo tracheal cells (EBTr) and mouse lung injury models. We found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…As bacterial LPS causes a variety of cell types to generate inflammatory cytokines, including IL 6 and IL 1, it has been widely employed to create an inflammatory model. [ 31 ]. It has been observed that ROS plays a dynamic role in mastitis and its pathophysiology [ 36 ], in lung injury, and in cancers [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As bacterial LPS causes a variety of cell types to generate inflammatory cytokines, including IL 6 and IL 1, it has been widely employed to create an inflammatory model. [ 31 ]. It has been observed that ROS plays a dynamic role in mastitis and its pathophysiology [ 36 ], in lung injury, and in cancers [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using commercially available kits, malondialdehyde concentrations were measured spectrophotometrically at 532 nm (Nanjing Jiancheng Bioengineering Institute, Nanjing, China). MDA activity was measured by a previously described technique, the thiobarbituric acid reaction method described by Chen et al [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that TNF‐α, IL‐1β, and IL‐8 are important pro‐inflammatory mediators in inflammatory responses, moreover, excessive release of the pro‐inflammatory cytokines play crucial roles in the pathogenesis and development of ALI. 21 , 22 , 23 CCNB1 and CDC2 are known to be important cell cycle regulatory proteins, and play key roles in promoting cell cycle progression. 24 , 25 Caspases, especially caspase‐3 and caspase‐9, are considered as crucial effectors of cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…N-acetyl-L-cysteine (NAC) is a thiol compound that can be directly used as a free radical scavenger and a precursor of reduced glutathione [ 8 ]. The antioxidant and anti-inflammatory actions of NAC in diverse respiratory diseases have been proved [ 9 ]. NAC is associated with alleviation in symptoms and delay in exacerbations of chronic obstructive pulmonary disease [ 10 ].…”
Section: Introductionmentioning
confidence: 99%